2006
DOI: 10.1183/09031936.00135205
|View full text |Cite
|
Sign up to set email alerts
|

BALF-derived fibroblasts differ from biopsy-derived fibroblasts in systemic sclerosis

Abstract: Growth of fibroblasts from bronchoalveolar lavage fluid (BALF) in patients with systemic sclerosis (SSc) has previously been described. The purpose of the present study was to characterise fibroblasts from BALF and bronchial biopsies from SSc patients with alveolitis and from controls, to analyse fibroblast proliferation, migration, stress fibres and proteoglycan production.BALF and bronchial biopsies were collected from 10 patients with SSc and alveolitis and from 15 controls.Outgrowth of fibroblasts was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
2
18
1
1
Order By: Relevance
“…The latter hypothesis is consistent with observations made in asthma or systemic sclerosis, where alveolar fibroblasts and interstitial fibroblasts obtained from the same patient exhibited different phenotypes [30][31][32]. We were not able to perform such a comparison as obtaining fibroblasts from BAL and biopsy in the same patient with ALI/ARDS was not possible in the clinical setting for ethical concerns.…”
Section: Critical Care and Lung Injury C Quesnel Et Alsupporting
confidence: 68%
“…The latter hypothesis is consistent with observations made in asthma or systemic sclerosis, where alveolar fibroblasts and interstitial fibroblasts obtained from the same patient exhibited different phenotypes [30][31][32]. We were not able to perform such a comparison as obtaining fibroblasts from BAL and biopsy in the same patient with ALI/ARDS was not possible in the clinical setting for ethical concerns.…”
Section: Critical Care and Lung Injury C Quesnel Et Alsupporting
confidence: 68%
“…13,17,18 This indicates that versican is most likely a marker not only for BOS but is also for pathologic wound healing processes. One major function of versican is to bind to hyaluronan, and it also has the capacity to absorb water molecules.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, in previous clinical studies of SSc-ILD, the increased percentage of eosinophils in bronchoalveolar lavage fluid (BALF) was associated with decreased lung diffusing capacity for carbon monoxide and increased mortality (Bouros et al 2002; Silver and Clements 2003). Hence, the inclusion criteria of patients in an important clinical trial yielded evidence of increased percentages of eosinophils in BALF (Tashkin et al 2006), and an outgrowth of fibroblasts was observed in patients with an increased percentage of eosinophils in BALF (Scheja et al 2007). In addition, in patients with bronchial asthma, we previously reported that the concentration of ECP and eosinophil-protein X (EPX) in sputum were higher than and significantly correlated with those in serum (Motojima et al 1995; Koseki et al 1996).…”
Section: Discussionmentioning
confidence: 99%